Schumann's Dichterliebe and early romantic poetics: fragmentation of desire - Perrey, Beate (Cambridge Cambridge University Press, 2002)
This book offers a theory of Romantic song by re-evaluating Schumann's Dichterliebe of 1840, one of the most enigmatic works of the repertoire. It investigates the poetics of Early Romanticism in order to understand the mysterious magnetism and singular imaginative energy that imbues Schumann's musical language. The Romantics rejected the ideal of a coherent and organic whole and cherished the suggestive openness of the Romantic fragment, the disconcerting tone of Romantic irony and the endlessness of Romantic reflection - thereby realising an aesthetic of fragmentation. Close readings of many songs from Dichterliebe show the singer's intense involvement with the piano's voice, suggesting a 'split Self' and the presence of the 'Other'. Seeing Schumann as the 'second poet of the poem' - here of Heine's famous Lyrisches Intermezzo - this book considers essential issues of musico-poetic intertextuality, introducing into musicology a hermeneutic that seeks to synthesise philosophical, literary-critical, music-analytical and psycho-analytical modes of thought.